Towards Integrating Physiological Data in UI/UX Design Learning and Engineering Education - Montri Phothisonothai; Korawit Orkphol; Natthapon Pannurat; Apirath Limmanee; Warayost Lamaisri; Chaowat Euafua (My University, 2024)
This paper introduces an educational framework for incorporating physiological data into engineering classroom activities to enrich the learning process of User Interface/User eXperience (UI/UX) design. Informed by Bloom’s Taxonomy and well-established software engineering design principles, this approach incorporates a variety of key advanced physiological technologies–including eye tracking, palm and fingers movements, brain wave monitoring, muscle movement, and virtual reality–into project-based learning (PBL) scenarios within human-machine interaction (HMI) design. We have analyzed six PBL initiatives in UI/UX design to evaluate the effectiveness of this method. Our findings suggest a transformative shift in engineering education, promoting a more cohesive, data-driven methodology in teaching and learning not only deepens understanding but also stimulates innovation in the field of UI/UX design, particularly within the context of HMIs.
Keywords: Biomedical and Engineering Education; Robotics and Automated Systems; E-Learning and Knowledge Management